Investigating middle school students' supporting reasons throughout written argumentation in the context of socio-scientific issue-based instruction - Akkaş, Büşra (My University, 2018)
The skills of argumentation have been gaining importance in science education recently. In order to achieve scientific literacy, students need the skills of thinking critically, making informed decision, developing arguments, etc. and socio-scientific issue-based instruction (SSI-based instruction) helps enhance these skills. Behind these skills, it is also important to understand what supporting reasons affect the process of making decision, developing arguments during argumentation. Therefore, the aim of this research is to examine the supporting reasons that the middle school students' use when they are writing arguments about a socio-scientific issue related to a gene editing method (CRISPR). In this research, an SSI unit (including argumentation), about CRISPR method was developed according to the SSI-based instruction model by Sadler, Foulk, Friedrichsen (2017). CRISPR method is used as the focal socio-scientific issue because of the dilemma among the researchers, countries, engineers, etc. about whether CRISPR method should be used or not. The main question of the unit was "How might using CRISPR method affect the future?" The unit was taught to 7th grade students who are studying in a middle school for 4 weeks. At the end of the unit, written arguments were collected. Qualitative approach was adopted to the research and SEE-SEP model was used as an analytical framework because of the multi-perspective feature of SSI. The model includes six subject areas (sociology/culture, economy, environment/ecology, science, ethics/morality, and policy) and three aspects (knowledge, value and personal experience). The supporting reasons that the students used in the written arguments were investigated from these aspects and the subject areas. It is revealed that students benefited from their science knowledge and value aspect when they need to decide about the use of CRISPR method in the future. Also, ethics/morality subject area is on the foreground in their written argumentation.

Son dönemlerde argümantasyon becerileri, fen bilimleri eğitiminde önem kazanmaktadır. Fen okur-yazarlığının gelişimi için öğrenciler eleştirel düşünme, bilgiye dayalı karar verme, argüman geliştirme gibi becerilere ihtiyaç duymaktadır ve sosyo-bilimsel konu temelli öğretim bu becerilerin gelişimine katkı sağlamaktadır (SBK-temelli öğretim). Bu becerilerin yanında, argüman geliştirme ve karar verme süreçlerini etkileyen destekleyici nedenleri anlamak da önem kazanmaktadır. Bu tezin amacı ortaokul öğrencilerinin sosyo-bilimsel konu olarak uyarlanan bir gen düzenleme yöntemi (CRISPR/Cas9) ile ilgili argüman yazarken kullandıkları destekleyici nedenleri incelemektir. Bu araştırmada Sadler, Foulk ve Friedrichsen (2017) tarafından SBK temelli öğretim modeli olarak geliştirilen model baz alınarak, argümantasyon yöntemini de içeren bir SBK ünitesi geliştirilmiştir. CRISPR/Cas9 yönteminin kullanımının bilim insanlarını, mühendisleri ve ülkeleri ikilemde bırakması, farklı düşünceleri barındırması nedeniyle, temel sosyo-bilimsel konu olarak CRISPR/Cas9 yöntemi üniteye uyarlanmıştır. Ünitenin temel sorusu “CRISPR yönteminin kullanımı geleceği nasıl etkiler?” olarak belirlenmiştir. Geliştirilen SBK ünitesi, 4 hafta boyunca bir devlet ortaokulunda okuyan yirmi sekiz 7. sınıf öğrencisine uygulanmıştır. Ünite sonunda ise, öğrencilerden konu hakkında görüşlerini belirten yazılı argümanlar toplanmıştır. Nitel araştırma yönteminin benimsendiği bu çalışmada, SBK’nın çok yönlü özelliğine vurgu yapan SEE-SEP modeli analitik çerçeve olarak kullanılmıştır. Bu model 6 konu (sosyoloji/kültür, ekonomi, çevre/ekoloji, bilim, etik/ahlak ve politika) ve 3 boyut (bilgi, değer ve kişisel deneyimler) içermektedir. Öğrencilerden toplanan yazılı argümanlar ise bu konular ve boyutlar baz alınarak incelenmiştir. İncelemeler sonucunda ise öğrencilerin argümanlarını yazarken sıklıkla bilimsel bilgi ve etik konularından, değer boyutundan yararlandıkları ve destekleyici nedenlerini bu konu ve boyutlara dayanarak oluşturdukları tespit edilmiştir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2018
Keywords: Sosyo-bilimsel konu (SBK); SBK temelli öğretim; CRISPR/Cas 9 yöntemi; Argümantasyon; SEE-SEP modeli; Socio-scientific issue (SSI); SSI-based instruction; CRISPR method; Argumentation; SEE-SEP model